Acute effect of five different stretching strategies on speed and agility parameters in recreationally active women - GENÇ, Harun; CİĞERCİ, Ali Erdem; AYDINLI, İbrahim (Faculty of Medicine, Universitas Trisakti, 2024)
BackgroundStretching includes movements that provide joint range of motion, increase the flexibility of muscles, joints, ligaments, and the speed of musculoskeletal communication, which are applied to increase performance in the main part of the training. Anaerobic properties are among the most important determinants of performance in athletes. Therefore, the objective of this study was to investigate the effects of five different stretching exercises on anaerobic performance (speed and agility parameters) in recreationally active women. MethodsA study of within-subject experimental design was conducted involving 30 recreationally active females aged 23.76 ± 1.50 years. Five different protocols (NS: no stretching; SS: static stretching; DS: dynamic stretching; SDS: static + dynamic stretching; DSS: dynamic + static stretching) were used to measure performance parameters after stretching exercises. After each stretching exercise, the 10 and 20 m sprint, Illinois agility test, and reactive agility test were used to determine anaerobic performance. Repeated measures analysis of variance (ANOVA) was employed for the analysis. ResultsA notable difference was observed in the 10 m and 20 m performance of recreationally active women after five different stretching protocols (p<0.05). When looking at the agility test values, it was found that a significant difference existed (p<0.05). DS showed the best performance in all tests. ConclusionAccording to these results, in recreationally active women, only SS should be avoided before high or explosive exercises, or the warm-up period should include only DS, or if a combined application is to be made, DS should be applied after SS.